2000
DOI: 10.1016/s0004-9514(14)60328-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ankle dorsiflexion on range and reliability of straight leg raising

Abstract: The effect of dorsiflexion was investigated on range of passive straight leg raising (SLR) and on inter-rater reliability with 35 patients reporting unilateral lumbar pain with or without ipsilateral leg symptoms. Ranges of SLR and SLR with dorsiflexion (SLR/DF) to onset of lumbar or leg symptoms (P1) were independently measured using a gravity goniometer by pairs of different physiotherapists at two clinics. Dorsiflexion significantly reduced SLR range by a mean of 9 degrees across both samples. Similar high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 31 publications
3
30
0
6
Order By: Relevance
“…The participant's leg 18 was lifted passively by the second test administrator into hip flexion. The ankle was kept in a relaxed 19 position throughout to minimize the influence of the gastrocnemius muscle (Boland and Adams, 2000). 20…”
Section: Methodsmentioning
confidence: 99%
“…The participant's leg 18 was lifted passively by the second test administrator into hip flexion. The ankle was kept in a relaxed 19 position throughout to minimize the influence of the gastrocnemius muscle (Boland and Adams, 2000). 20…”
Section: Methodsmentioning
confidence: 99%
“…12 Ankle dorsiflexion is a common sensitizing maneuver for SLR testing. 5,12,18 Studies in rats and dogs have demonstrated increased strain (elongation) in the sciatic nerve at the proximal thigh when ankle dorsiflexion was added to SLR testing. 1,7 Further support for the use of ankle dorsiflexion as a sensitizing maneuver is provided by findings from a cadaveric study, 12 in which prepositioning the ankle in dorsiflexion created distal movement in the tibial nerve at the knee and ankle.…”
Section: Clinical Assessment Sessionmentioning
confidence: 99%
“…Clinically, prepositioning the ankle in dorsiflexion leads to a reduction of hip range of motion during SLR testing, when taken to maximal resistance to hip flexion in people with low back pain and healthy individuals. 5 Neurodynamic testing can also produce increases in local muscle tone. SLR testing without ankle dorsiflexion has been shown to induce hamstring and gluteal muscle activity when the hip flexion is held at the maximally tolerated position.…”
Section: Clinical Assessment Sessionmentioning
confidence: 99%
See 1 more Smart Citation
“…
2Maidstone and Tunbridge Wells NHS Trust, UK, 3 Beckenham Physiotherapy, Sports and Acupuncture Clinic, UK, 4 Frimley Park Hospital NHS Foundation Trust, UK Study design: Randomized, single blind, same subject crossover trial. Objectives: To compare the effects of two neurodynamic treatment doses on range of hip flexion (ROM HF) and electromyographic (EMG) activity of semitendinosus, at first onset of pain (P1).
…”
mentioning
confidence: 99%